1992
DOI: 10.1007/bf00231666
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic finger movements in a skilled motor task

Abstract: When skilled typists strike one key, typically all of the fingers of one hand are in motion simultaneously. We studied the extent to which the motion of the individual fingers was similar. Subjects were asked to type lists of words, each word designed so that only one key would be pressed by a finger of one hand, the remaining letters being typed with the other hand. Changes in the lengths (flexion-extension) and orientation (abduction-adduction) of each finger were measured and the similarity of the motion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…Other observations reinforce the conclusions we reached from our study of typing, namely, the two hands generally move independently of each other Fish and Soechting 1992). While there were many instances in which the fingers of each hand depressed keys virtually simultaneously, there were also instances in which there was definite asynchrony in the times of key-on for notes that were intended (by the composer) to be synchronous.…”
Section: Control Of Bilateral Timing Of Keypressessupporting
confidence: 78%
“…Other observations reinforce the conclusions we reached from our study of typing, namely, the two hands generally move independently of each other Fish and Soechting 1992). While there were many instances in which the fingers of each hand depressed keys virtually simultaneously, there were also instances in which there was definite asynchrony in the times of key-on for notes that were intended (by the composer) to be synchronous.…”
Section: Control Of Bilateral Timing Of Keypressessupporting
confidence: 78%
“…Although it is generally assumed that fingers move independently, it has been shown that humans hardly ever move one finger alone (Fish and Soechting 1992;Soechting and Flanders 1992;Engel et al 1997). Co-activation in muscles not related to the movement has, in part, a central cortical origin (HagerRoss and Schieber 2000;Slobounov et al 2002), which we refer to as unintentional co-activation.…”
Section: Introductionmentioning
confidence: 93%
“…Hand motion studies involving simple activities such as reach-to-grasp (Santello et al, , 2002Mason et al, 2001;Braido and Zhang, 2004), and skilled activities such as typing (Fish and Soechting, 1992;Soechting and Flanders, 1997) or finger-spelling (Jerde et al, 2003;Weiss and Flanders, 2004), reveal that a small dimensional space accounts for a large fraction of the postural variance observed during these tasks. Even individuated finger movements, which are the hallmark of any skilled activity, occur with synergistic couplings with adjacent digits (Schieber, 1995;Hager-Ross and Schieber, 2000).…”
Section: Introductionmentioning
confidence: 99%